PERAN PROTOKOLER SEKRETARIAT DAERAH DALAM MENUNJANG KEGIATAN SEREMONIAL GUBERNUR KALIMANTAN TIMUR - Wildan Taufik (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the role of the Regional Secretariat Protocol in supporting the Performance of the Governor of East Kalimantan. Defined research focuses are : The Protocol role as a regulator of events, the Protocol role as a regulator of the working visit, and the Protocol role as the reception of local government and also the supporting factors and obstacle factors of the Protocol role in supporting the performance of the Governor of East Kalimantan. Sources of the data taken from the key informants such as The Assistant Public Welfare, Head of the protocol, Head of Public Relations and also informant such as Head of the Sub-part of the ceremony and trip leader, Head of the sub reception of local government and some staff protocols. Analisis data used interactive model developed by Milles, Huberman and Saldana through the stages.